The Implementation of Cooperative Learning Type Team Game Tournament (TGT) on Student Activity - Nadlrah Naimi; Nikmatul Khoiriyah Daulay; Melyani Sari Sitepu; Nurmayani (Journal of Psychology and Instruction, 2025)
The problem in this study is the lack of student activity in science lessons. This study aims to determine the effect of implementing Cooperative Learning Type Team Game Tournament (TGT) on Student Activity in Science Learning Class IV. The research approach used in this study is a quantitative approach with a pretest-posttest control group design. The data collection technique uses a non-test with an observation sheet research instrument to measure student activity. Instrument validation is carried out with expert validation. To test the research hypothesis, the researcher used the Independent T-Test. The results of the study showed that the sig value (0.000) <a (0.05) which means that there is an effect of cooperative learning type Team Game Tournament (TGT) on student activity. It can be concluded that implementing a cooperative learning type Team Game Tournament (TGT) affects student learning activity.